1980
DOI: 10.1055/s-0038-1650008
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ristocetin-Cofactor in Acute Myocardial Infarction: a Component of the Acute Phase Reaction

Abstract: SummaryWhen compared to the values obtained in healthy normal-weight, normolipemic controls, the plasma level of ristocetin-cofactor (VIII: R-cof.) was found to be much higher in patients with acute myocardial infarction and in postoperative conditions (4–5 days after a major surgical intervention). A lesser increase of VIII: R-cof. was noted in atherosclerotic patients without acute occlusive accidents and no significant changes of this plasma factor could be observed in hyperlipemic subjects without obvious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…We found that, in men, von Willebrand factor was related to the ABPI. Likewise, several case-control studies of peripheral arterial disease have reported higher levels in the cases (8,16,17). The ARIC study (18) reported associations between increased baseline von Wille brand factor and prevalent cases of stroke, coronary heart disease and peripheral arterial disease.…”
Section: Discussionmentioning
confidence: 99%
“…We found that, in men, von Willebrand factor was related to the ABPI. Likewise, several case-control studies of peripheral arterial disease have reported higher levels in the cases (8,16,17). The ARIC study (18) reported associations between increased baseline von Wille brand factor and prevalent cases of stroke, coronary heart disease and peripheral arterial disease.…”
Section: Discussionmentioning
confidence: 99%
“…The circulating levels of von Willebrand factor, plasminogen activator inhibitor-1 and C-reactive protein increase during the acute-phase that follows myocardial infarction (20)(21)(22)(23)(24). The induction of these factors is probably triggered by soluble inflammatory mediators, such as interleukin-1 and tumour ne crosis factor (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…According to clinical observation and laboratory data it was considered that the increase of plasmatic level of von Willebrand factor in patients with myocardial infarction is more likely a consequence of the reaction of endothelial cells to adrenergic and proinflammatory stimuli, rather than a simple leakage of vWF from injured endothelia (8). This interpretation is accepted and cited by many authors such as Schorer et al (9), Pottinger et al (10) It is worth mentioning that some genetic hemostasis defects were detected by the research group in Cluj Napoca.…”
Section: Reflectionsmentioning
confidence: 99%